DIGITAL TRANSFORMATION AND ITS IMPACT ON TAX ADMINISTRATION - Palomares Canales, Luis Alberto (2026)
Digital transformation has become increasingly relevant within the Peruvian tax administration as a mechanism for modernizing tax control, auditing processes, and the provision of public services. In this context, the objective of this study was to analyze the incidence of digital transformation on the Peruvian tax administration, considering developments observed at both national and international levels. The research adopted a quantitative approach with a descriptive scope and was based on documentary analysis of reports issued by the Organisation for Economic Co-operation and Development (OECD), the National Superintendency of Customs and Tax Administration (SUNAT), and recent scientific literature on digital government and tax modernization. The findings reveal significant progress in tax digitalization, particularly through the widespread adoption of electronic invoicing, electronic accounting records, the implementation of the Integrated System of Electronic Records (SIRE), and the development of digital platforms aimed at taxpayer assistance and tax enforcement. Furthermore, electronic invoicing increased reported sales by 7.4%, reported purchases by 5.5%, and VATrelated tax obligations by more than 5%, while more than 83 million electronic invoices were validated in Peru during 2024. The study concludes that digital transformation has a positive impact on the efficiency of the Peruvian tax administration by strengthening transaction traceability, tax control, and tax compliance. Nevertheless, important challenges remain regarding institutional interoperability, comprehensive process automation, and digital inclusion. It is recommended to enhance integration between public and private information systems, expand the use of artificial intelligence tools, and promote digital capacity-building programs for taxpayers and public officials.